Factors Influencing Language Shift in The Educational Domain Among International Class Students at Yayasan Slukat Learning Center - Bayuni, Ni Luh Meita; Netra , I Made; Krisnawati, Ni Luh Putu (Denpasar Institute, 2025)
The language shift could happen in the international class students when they interact with each other because English is not the only language the international class students are fluent in. This study aims to analyze the factors influencing the language shift in these international class students. This study used the international class students in Yayasan Slukat Learning Center as the data source. A questionnaire was administered to gather data from respondents. The questionnaire contained a set of questions designed to reveal the objectives of the study. To analyze the data, a mixed-method approach was applied in this research and presented using the informal and formal method. The research questions were addressed using the theory of factors of language shift proposed by Holmes. The findings reveal that participant, setting, topic, and function are key contributing factors to language shift, with topic identified as the most influential in this context.